Penilaian Kinerja Koperasi Dalam Perspektif Hukum Positif Di Indonesia - Suprihantosa Sugiarto (WADIAH, 2022)
This study aims to determine the regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises in question are: 1) Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises Number 06/Per/Dep.6/IV/2016 concerning guidelines for health assessment of savings and loan cooperatives and savings units borrow. Based on this regulation, cooperative performance is measured from 7 aspects, namely: capital aspect, productive asset quality aspect, management aspect, efficiency aspect, liquidity aspect, independence and growth aspect and cooperative identity aspect; 2) Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises Number 07/Per/Dep.6/IV/2016 concerning guidelines for the health assessment of savings and loan cooperatives and sharia financing and savings and loan units and cooperative sharia financing. Based on this regulation, the performance of cooperatives is measured from 8 aspects, namely seven aspects are the same as conventional cooperatives with different indicators plus one other aspect, namely the aspect of compliance with sharia principles.. Keyword: Performance, Cooperative Performance, Cooperative Health.